Transcriptome-Wide m6A Methylome and m6A-Modified Gene Analysis in Asthma - Sun, Deyang; Cai, Xiaolu; Shen, Fenglin; Fan, Liming; Yang, Huan; Zheng, Suqun; Zhou, Linshui; Chen, Ke; Wang, Zhen (Frontiers in Cell and Developmental Biology, 2022)
N6-methyladenosine (m6A) modification is one of the most prevalent RNA modification forms and is an important post-transcriptional mechanism for regulating genes. In previous research, we found that m6A regulator-mediated RNA methylation modification was involved in asthma, however, the specific modified genes are not clear. In this study, we systematically evaluated the transcriptome-wide m6A methylome and m6A modified genes in asthma. Here we performed two high-throughput sequencing methods, methylated RNA immunoprecipitation sequencing (MeRIP-seq) and RNA sequencing (RNA-seq) to identify key genes with m6A modification in asthma. Through difference analysis, we found that 416 methylation peaks were significantly up-regulated and 152 methylation peaks were significantly downregulated, and it was mainly distributed in 3'UTR. Furthermore, compared with the control group, there were 2505 significantly up-regulated genes and 4715 significantly down-regulated genes in the asthma group. Next, through the combined analysis of transcriptome and differential peak, 14 differentially expressed genes related to RNA methylation modification were screened. Finally, through 87 health controls and 411 asthma cases from the U-BIOPRED (Unbiased Biomarkers for the Prediction of Respiratory Disease Outcomes) program, we verified three m6A modified key genes (BCL11A, MATK, and CD300A), and found that they were mainly distributed in exons and enriched in 3'UTR. Our findings suggested that intervening in m6A modified genes may provide a new idea for the treatment of asthma.